Juvenile justice and rehabilitation- correctional work with juvenile offenders in closed institutions. (The Journal of Psychology and Sociology, 2015)
The article deals with the concept of «juvenile justice», examines the experience of children’s judges system of foreign countries, describes the factors of deviant behavior, proposes rehabilitation and correctional work program for minors in prison. Provides an explanation of the legislation system with positive changes in order to implement the project «Juvenile justice» and «Concept of development of the juvenile justice system in the Republic of Kazakhstan». The article examines children’s judges which are based on the foreign experience. The short summary of the AngloSaxon and Continental models of foreign countries are given. It describes the fac tors of deviant behavior, as well as reveals signs of demoralization in the behavior of minors which are rapid growth of alcoholism, drug addiction, vagrancy, disorderly conduct, theft, robbery, prostitution, suicide. Char acteristics of juvenile offenders by the typological features and the main types of social exclusion are described.
Keywords: juvenile justice; children’s courts; the justice system; devi ant behavior; behavioral problems; criminal behavior; antisocial groups deviant adolescents; social isolation; closed institutions; psychological and pedagogical work; juveniles; readaptation